To be where you are (Thorndike Press large print basic, ,, 2017)
After twelve years of wrestling with the conflicts of retirement, Father Tim Kavanagh realizes he doesn't need a steady job to prove himself. Then he's given one. As for what it proves, heaven only knows. It's life as usual in Mitford. A beloved town character lands a front-page obituary, but who was it, exactly, who died? And what about the former mayor, born the year Lindbergh landed in Paris, who is still running for office? All this, of course, is but a feather on the wind compared to Muse editor J.C. Hogan's desperate attempts to find a cure for his marital woes. Will it be high-def TV or his pork chop marinade? Twenty minutes from Mitford at Meadowgate Farm, newlyweds Dooley and Lace Kavanagh face a crisis that devastates their bank account and impacts their family vet practice. But there is still a lot to celebrate, as their adopted son, Jack, looks forward to the most important day of his life -- with great cooking, country music, and lots of people who love him. Happily, it will also be a day when the terrible wound in Dooley's biological family begins to heal because of a game -- let's just call it a miracle -- that breaks all the rules.

Shepherds abiding: a Mitford Christmas story (Mitford years, ,, 2003)
Having pursued intellectual matters all of his life, Father Tim discovers the joys of working with his hands when he discovers a worn-out nativity scene and begins to restore it.

To be where you are (Mitford years, ,, 2017)
Father Tim Kavanagh struggles to find meaning in retirement, while newlyweds Dooley and Lace face a crisis that drains their bank account, and four-year-old Jack Tyler looks forward to the biggest day of his young life.

Light from heaven (Mitford years, ,, 2005)
The final volume in the Mitford Years series finds Father Tim contemplating the revival of a remote mountaintop church, a challenge he hopes will be his ultimate calling, but fears will be an impossible task.

Come rain or come shine (The Mitford Years, 11,, 2015)
"Over the course of ten Mitford novels, fans have kept a special place in their hearts for Dooley Kavanagh, first seen in At Home in Mitford as a barefoot, freckle-faced boy in filthy overalls. Now, Father Tim Kavanagh's adopted son has graduated from vet school and opened his own animal clinic. Since money will be tight for a while, maybe he and Lace Harper, his once and future soul mate, should keep their wedding simple. So the plan is to eliminate the cost of catering and do potluck. Ought to be fun. An old friend offers to bring his well-known country band. Gratis. And once mucked out, the barn works as a perfect venue for seating family and friends. Piece of cake, right?" --